Comparison of Transforming Growth Factor 1 (TGF-β1) Expression in Various Lysate Platelet-Rich Fibrin (L-PRF) Concentrations on Human Dental Pulp Stem Cell Differentiation - Muhammad Zaal Haq; Anggraini Margono; R. A. H. Nilakesuma Djauharie; Dini Asrianti; Indra Topanesa; Indah Julianto (Association of Support to Oral Health Research (APESB), 2021)
Objective: To compare Transforming growth factor-β1 (TGF-β1) expression in various L-PRF concentrations on the hDPSC differentiation process. Material and Methods: hDPSC cell cultures were subjected to serum starvation by reducing FBS levels in the hDPSC culture media. Lysate PRF was obtained from the PRF gel, which was then incubated at 4°C for 24 h. The supernatant was dried, transferred to a 2-ml Eppendorf tube, and stored at −20°C. The evaluation of TGF-β1 expression in 1%, 5%, 10%, and 25% L-PRF samples and 10% FBS (control) during the process of hDPSC differentiation was quantified using an ELISA reader on day 7. The expression of TGF-β1 was subjected to a one-way ANOVA test, followed by Bonferroni's post hoc test with significant values (p<0.05). Results: Significant differences were noted in TGF-β1 expression between 1%, 5%, 10%, and 25% L-PRF and the control group (10% FBS). The highest TGF-β1 expression occurred with 25% L-PRF (0.645 ± 0.048), followed by 10% L-PRF (0.461 ± 0.035), 10% FBS (0.374 ± 0.013), 5% L-PRF (0.275 ± 0.045), and the lowest expression was with 1% L-PRF (0.160 ± 0.045). Conclusion: The best result of TGF-B1 expression in hDPSC differentiation was in the 25% L-PRF group.